Viruses in our world - Wood, John, 1990- (New York, NY KidHaven Publishing, 2020)
Viruses aren't like anything else you can see under a microscope. Is a virus a living thing or something else? Readers explore the answer to this question as they examine viruses, learning what they look like and how they affect us. As readers discover important facts about how viruses multiply and what sicknesses they cause, they expand their knowledge of essential parts of science curricula, including beginner biology concepts.
What are viruses? -- What is a microscope? -- Influenza -- Ebola -- Good viruses -- Vaccines.
Includes index.
108230
Keywords: Viruses -- Juvenile literature; Microscopy -- Juvenile literature; Juvenile works